MEMPIDANAKAN PARA WHISTLEBLOWER KORUPSI - Awaludin, Arif - (Universitas Nurul Jadid, 2022)
Whistleblowers are often victims of retaliation. Retaliation is basically a negative result of uncovering wrongdoing or crimes in the workplace, including corruption. The main problem in this study is the reality of victims of retaliation for whistleblowing actions carried out by the whistleblower and also the legal protection system for the whistleblower who uncovers a criminal act of corruption. The methodology of this research is socio legal with a qualitative approach. Retaliation against whistleblowers does not only result in mental suffering, but also physical suffering resulting in quitting work or being fired from work. Legal protection in Indonesia is very limited, both regulatory and law enforcement bureaucracy.Keywords: criminalize, whistleblower, corruption